(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In recent years, large-scale and consistent reforms have been implemented in our country to increase energy efficiency in economic sectors and the social sphere, to develop the use of renewable energy sources, and legal frameworks related to energy development have been created.